2020
DOI: 10.2174/1573399815666190405171907
|View full text |Cite
|
Sign up to set email alerts
|

Study of Possible Relation between Fasting Plasma Glucagon, Gestational Diabetes and Development of Type 2 DM

Abstract: Background and Aims: Women who develop GDM (gestational diabetes mellitus) have a relative insulin secretion deficiency, the severity of which may be predictive for later development of diabetes. This study aimed to investigate the role of fasting plasma glucagon in the prediction of later development of diabetes in pregnant women with GDM. Materials and Methods: The study was conducted on 150 pregnant women with GDM after giving informed oral and written consents and being approved by the research ethical c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…A handful of studies have suggested that hyperglucagonaemia may precede insulin resistance to disrupt glucose tolerance in GDM. 5,[30][31][32] Several limitations should be noted in our study. First, the sample size may be considered relatively small, but the primary outcomes of our study were clear-cut.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…A handful of studies have suggested that hyperglucagonaemia may precede insulin resistance to disrupt glucose tolerance in GDM. 5,[30][31][32] Several limitations should be noted in our study. First, the sample size may be considered relatively small, but the primary outcomes of our study were clear-cut.…”
Section: Discussionmentioning
confidence: 90%
“…Augmented glucagon levels would be counterproductive in terms of controlling blood glucose in GDM. A handful of studies have suggested that hyperglucagonaemia may precede insulin resistance to disrupt glucose tolerance in GDM 5,30–32 …”
Section: Discussionmentioning
confidence: 99%
“…Our results agree with previous works reporting that alpha-cell dysfunction, evaluated by higher levels of glucagon, precedes T2DM development. 8,9,48,49 Other studies have also described that patients with a higher postprandial level of the glucagon:insulin ratio presented a higher probability of developing T2DM. 10,50 These results suggest that the use of challenge tests such as the OGTT are more suitable than static measurements in assessing the individual phenotypic flexibility and the potential risk of developing the metabolic disorder.…”
Section: ■ Discussionmentioning
confidence: 97%
“…One value in B (PV) was obtained by ELISA instead of RIA (Hussein et al, 1986). The data were compiled from the following references: A (Species)–Humans (H): Bolli et al (1984), Borghi et al (1984), Brodows (1985), Evans et al (2004), Fujita et al (1975), Gosmanov et al (2005), Hamaguchi et al (1991), Hansen et al (1982), Heise et al (2004), (2004), Henkel et al (2005), Jaspan et al (1984), Kalkhoff et al (1973), Livingston et al (1985), Okba et al (2020), Petersen and Sullivan (2001), Porcellati et al (2003), Raju and Cryer (2005), Sherwin et al (2005), Tasaka et al (1980), Verillo et al (1988); Dogs (D): Cersosimo et al(1998), Coker, Koyama, Brooks, et al (1999), Kraft et al (2017), Ishida et al (1983), Moore et al (2014), Sherck et al (2001), Sindelar et al (1998), and Vaitkus et al (1984); Rats (R): Balks and Jungermann (1984), Charbonneau et al (2005), Langhans et al (1984), Latour et al (1999), Mayor and Calle, (1988), Omer et al (2004), Powell et al (1993), Ruiter et al (2003), Unger (1985), Widmaier et al (1991) and Winzell et al (2007), Mice (M): Green et al (2016), Karlsson et al (2002), Marty et al (2005), Parker et al (2002), Perry et al (2020), Winzell et al (2007) and Zhang et al (2018) B (Vascular Bed) ‐ Hepatic Portal (HP): See legend, Figure 1, Peripheral Venous (PV): Balks and Jungermann (1984), Bolli et al (1984), Cersosimo et al (1998), Charbonneau et al (2005), Coker, Koyama, Brooks, et al (1999…”
Section: Plasma Glucagon Concentrationsmentioning
confidence: 99%